Darfur - Dimensions of Challenge for Development : Background Volume - World Bank (Washington, DC, 2013)
This background volume is not about the recent conflict, nor the humanitarian situation in Darfur today. Rather, it adopts a longer term perspective in an attempt to understand the range of underlying structural obstacles to growth and prosperity in the region. The World Bank, in collaboration with a range of stakeholders, has investigated the nature and extent of the underlying structural obstacles to the region's development. This background volume presents the results of the work of several teams, drawing on primary and secondary sources and field work undertaken in the latter half of 2006. The aim is to help re-establish a knowledge base across multiple dimensions, to inform future development planning oriented toward broad-based growth and attainment of the millennium development goals. The report provides a diagnosis of existing constraints: the basic thesis is that redressing marginalization is central to effectively overcome the challenges to peace and prosperity in the region, and thus in the Sudan overall. The immense challenges facing Darfur reflect not only the immediate conflict, but a series of major structural factors that can be traced back over decades. Of foremast importance is the failure of national policies and development projects to promote broad-based development and good governance. Geographic and demographic factors, in particular increasing desertification, periodic droughts and rapid population growth - have exemplified the, challenges, but the underlying failure of institutions to function in ways that are accountable to the people, and conducive to pro-poor development, plays a critical explanatory role.